2020
DOI: 10.47577/tssj.v7i1.394
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Lockdown Measures on Least Developing Economies in Africa-a case of Malawi Economy

Abstract: The outbreak of COVID-19 pandemic has caused the entire world at standstill affecting all the sectors of economies in the whole world. In order to reduce the spread of the cases and the mortality rate of this pandemics many economies have implemented a lot of social distancing measurers with the aim of separating people direct and indirect contacts as the Virus can be transferred through physical contact and is also an airborne, these isolations measures have proved to be effective in many countries. One of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…13 This improvement on knowledge gaps can be further explained due to the devastating impacts that COVID-19 has brought which is evidenced in everyday life, especially those social distance measures like lockdown has really made its awareness go viral. 2 ICT has proved to be contributing immensely to all the sectors development through the way and speed information could be transferred from one person to another. The study found a similar pattern and revealed that the Internet, through social media platforms, was the main source of information the international students used to know about COVID-19, seconded by the school notifications, which universities in China usually issued to apprise them of COVID-19 updates either weekly or monthly depending on the need of the institutions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13 This improvement on knowledge gaps can be further explained due to the devastating impacts that COVID-19 has brought which is evidenced in everyday life, especially those social distance measures like lockdown has really made its awareness go viral. 2 ICT has proved to be contributing immensely to all the sectors development through the way and speed information could be transferred from one person to another. The study found a similar pattern and revealed that the Internet, through social media platforms, was the main source of information the international students used to know about COVID-19, seconded by the school notifications, which universities in China usually issued to apprise them of COVID-19 updates either weekly or monthly depending on the need of the institutions.…”
Section: Discussionmentioning
confidence: 99%
“… 13 This improvement on knowledge gaps can be further explained due to the devastating impacts that COVID-19 has brought which is evidenced in everyday life, especially those social distance measures like lockdown has really made its awareness go viral. 2 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malawi is a landlocked country located in the southern part of Africa bordering Zambia to the west, Mozambique to the south-west, and Tanzania to the north (Figure 1). The vast majority of the country's population depends on agriculture and most of these live under the poverty line whose income usually depend on loans for farming and conducting small scale business (Munthali & Xuelian, 2020b, 2020a. The study adopted a crosssectional survey design in which data was collected using a Google form that was sent online via social media platforms like WhatsApp, Facebook, and email on the rst week of September 2020 to 31st December 2020.…”
Section: Study Design and Settingmentioning
confidence: 99%
“…Training Centre, Miracle Technical and Mzuzu Technical College. Malawi is located in the southern part of Africa bordering Tanzania, Zambia Mozambique and Zimbabwe with a total population close to 19,413,262 with the majority of its people depending on education and Agriculture (Centres for DiseaseControl and Prevention, 2019;Munthali & Xuelian, 2020;Ngwira & Watanabe, 2019;WPR, 2020).…”
mentioning
confidence: 99%